Distribution and Variability of Pseudocercospora griseola in Uganda - Ddamulira, G.; Mukankusi, C.; Ochwo-Ssemakula, M.; Edema, R.; Sseruwagi, P.; Gepts, P. (Journal of Agricultural Science, 2012)
is highly variable with many different races occurring in different agro-ecological zones. Therefore, for an effective breeding program, there is a need to continuously monitor the distribution and variability of the pathogen as a means of guiding breeders on which races to target. A study was conducted to assess the incidence, severity and variability of P. griseola in bean growing districts of Dokolo, Lira, Apac, Sironko, Mbale, Rakai, Lwengo, Bukomansibi, Kabale and Kisoro in Uganda. Forty five out of 80 isolates collected were tested on a set of 12 international bean differentials cultivars for ALS. Molecular markers were also used to elucidate the variability among isolates. In all districts, ALS was found wide spread with a mean incidence of 49.9%. Dokolo district had the highest disease incidence and severity, while Kisoro registered the lowest values respectively. In terms of altitude, incidence (60%) and severity (45%) were high for bean fields located between 1000-1200 m and low disease incidence (33.6%) and severity (20.7%) for fields lying above 1500 m. The standard differential cultivars and molecular markers defined 12 pathotypes and 30 haplotypes respectively. These belonged to Middle America and Andean group with considerably high level of diversity. Our findings indicated the presence of ALS in Uganda with high incidence, severity and variability across districts and altitudes. Hence strategic interventions involving integrated disease management and breeding for durable resistance are required to manage the disease.
Keywords: Pseudocercospora griseola; Incidence; Severity & variability